Harmonization of global third generation mobile systems. - Zeng, M.
The International Telecommunication Union launched the third-generation project in 1986 with the aim to provide global personal communication using an inexpensive mobile terminal that can truly facilitate communication "anywhere, anytime". In previous years, standardization activities toward IMT-2000 have accelerated toward concrete specifications. By June 1998, a total of 15 proposals from around the world had been submitted to the ITU as radio transmission technology candidates. Since then, the 3G standardization landscape has seen many changes-a steady progression of the convergence process. This article provides a comprehensive overview of the worldwide harmonization efforts on the standardization of third-generation terrestrial mobile communication systems. The status, as of October 1999 when this article was written, of the technical specifications within 3G partnership projects are also summarized.
Keywords: 3G partnership projects; 3G standardization activities; 3G standards; CDMA; IMT-2000.; ITU; International Telecommunication Union; Global personal communication; Global third generation mobile systems; Mobile terminal; Radio transmission technology; Technical specifications; Third-generation project; Third-generation terrestrial mobile communication systems; Worldwide harmonization efforts